Deep water properties in the North Atlantic's eastern and western basins during the Mid-Brunhes (330-630 ka) - Voelker, Antje H. L. (2016)
European Geosciences Union General Assembly 2009 (EGU 2009), Vienna, Austria, April 19-24, 2009